Disinformasi di Era Post-Truth: Ancaman terhadap Demokrasi dan Mobilitas Global - Salma Nabila Rianissa (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2025)
The Post-Truth phenomenon has posed significant challenges to global democracy, particularly through the spread of disinformation that undermines public trust in political institutions and democratic processes. In this era, emotions and personal beliefs are prioritized over objective facts, exacerbating political polarization and creating an environment where hoaxes and disinformation can influence political decisions and citizen participation. Furthermore, the Post-Truth era impacts global mobility, as disinformation on issues such as migration, international policies, and ethnic identity heightens tensions between nations and threatens the integrity of international policies. This research aims to explore how disinformation in the Post-Truth era poses a threat to the stability of democracy and global mobility. Using a literature review method from various academic sources, this article analyzes the impact of disinformation on political processes, security, and international relations in the digital era. The findings indicate that disinformation significantly damages democracy and hinders global mobility, highlighting the need for collective measures to combat this threat.